RIFM fragrance ingredient safety assessment, tetrahydro-4-methyl-2-(2-methylpropen-1-yl)pyran, CAS Registry Number 16409-43-1. (December 2017) - Api, A.M.; Belsito, D.; Bhatia, S.; Botelho, D.; Browne, D.; Bruze, M.; Burton, A.; Buschmann, J.; Calow, P.; Dagli, M.L.; Date, M.; Dekant, W.; et al.
Highlights: Tetrahydro-4-methyl-2-(2-methylpropen-1-yl)pyran safety assessment based on RIFM's criteria. Safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data and/or TTC.